The effect of English song in vocabulary masteri - Mayla Kara Millah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: Vocabulary is the basic language aspects that that function as building the blocks of a language and It is important develop vocabulary. Still, vocabulary is too vast to be learned only at classroom and exposing students to English outside the classroom activities are an effective method to develop vocabulary. English songs is an authentic source of English that is commonly exposed to students. Therefore, this study aims to identify the effect of students’ frequency in listening to English songs on their vocabulary mastery. This study was implemented using an experimental quantitative research design using an online questionnaire delivered via Google Form to 40 fourth-semester students of the English department at University of Islam Malang. The data in this study are analyzed using paired sample t-test to measure the difference of pre-test and post-test scores after the treatment. The result concludes that listening to English songs have a positive effect on students’ vocabulary mastery. The data shows that the mean score of vocabulary mastery after a week of treatment using English songs are higher compared to the first vocabulary mastery test before the treatment. The mean score is increased by 3.812 points with very significant value of 0.008 which is significant at 0.01 and considered to be very significant. Therefore, the result confirms the hypothesis alternative that stated listening to English songs have an impact in students’ vocabulary mastery. It is suggested for future studies to conduct more study on the effect of other aspects in songs such as tempo, genre to vocabulary mastery for deeper understanding of the effect of specific types of songs on vocabulary developmen